An insight into the profile characteristics and technical batting skill of adolescent cricket players - Clark, Matthew Edward (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2016)
Background: Current traditional cricket practices incorporate the use of a netted-off pitch to provide cricket players the opportunity to hone their skills with bat and ball. The lack of ecological validity of these training environments results in the absence of important task and environmental constraints which influences the manner in which the sport is played. Objectives: The purpose of the current research was two-fold: firstly, it aimed to establish a profile database of adolescent cricket players in the Eastern Cape province of South Africa; and secondly, it aimed to investigate the efficacy of a constraints-led training intervention on skill development in adolescent cricket batsmen. Methods: Study I required 90 participants (u13: n = 40; u15: n = 50) to perform measures pertaining to anthropometric, morphological, flexibility and physical performance characteristics. This included stature, mass, body composition, limb length, flexibility, agility, and power measures. Study II was a case-control study (u15: n = 24), whereby the experimental group (n = 12) was exposed to a constraints-led batting protocol during the course of the cricket season. The objective of the protocol was to encourage the manipulation of the ball around the playing field. Pre- and post-intervention measures were performed using a batting skills test, which assessed batsmen's capability to manipulate the ball to various areas of the playing field. Results: Study I revealed significant differences (p <0.0001) in stature, mass, limb length and power variables when comparing the u15 age group with the u13 age group. No differences were recorded for agility. The u13 age group had greater linear correlations for the variables of interest compared to the u15 age group. Study II revealed no differences in technical skill between the experimental group and the control (p <0.315).. The tests also revealed that adolescent batsmen favoured hitting deliveries through the extra-cover scoring zone. The third-man and fine-leg scoring zones were least preferred to hit deliveries through. A number of limitations to the study design resulted in the inability to determine the efficacy of a constraints-led batting protocol on skill development in an adolescent batting cohort. Conclusion: The results of study I indicated that the onset of puberty played an important role in the measures and performances between the u13 and u15 age groups. The results of study II indicated that adolescent batsmen are not adept at manipulating the ball around the field. Recommendations are provided for both studies.
Keywords: Uncatalogued